Edukasi masyarakat dalam menangani luka dan kegawatdaruratan sehari-hari pada anak stunting dengan memanfaatkan tanaman obat keluarga - Darajat, Agus Mi'raj; Abidin, Imam; Khotimah, Nur Intan Hayati Husnul; Tambunan, Irisanna; Megawati, Sri Wulan (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Overall, Sinarjaya Village consists of 10 RW, and supported by good soil conditions, more people are suitable for farming and working in factories. Based on the Garut Regional Government, the prevalence of stunting is targeted to be below 14% in 2024, in accordance with the national target, although the stunting rate in Garut Regency increased from 23.6% to 24.1% in early 2024 based on the Indonesian Health Survey. Purpose: To improve community skills related to daily emergencies and the use of family medicinal plants for wounds through community empowerment in families with stunted children. Method: The implementation of activities involves residents involved as Family Welfare Empowerment Cadres and Integrated Service Post Cadres in Sinarjaya Village, Tarogong, Garut. Participation in increasing community empowerment efforts in handling daily emergencies and understanding related to the use of Family Medicinal Plants for wounds in stunted children in families in particular. Activities are carried out through several stages, namely preparation, implementation, and evaluation. Results: Cadres can make phone calls well and can answer questions about emergency handling well. Training in the form of mini lectures and direct practice can improve skills towards cognitive, affective, and basic behavioral aspects such as the ability to remember, pay attention and control performance. Conclusion: Education through training and simulation can improve cadres' knowledge and skills in handling daily emergencies and the use of TOGA for wounds. Improved skills can improve preparedness and success in handling emergencies. The role of PKK and Posyandu cadres who can reach the community is the basis for efforts to empower individuals and families so that handling will be faster and more appropriate. Keywords: Community Empowerment; Dwarfism; Family Medicinal Plants; Wound Care. Pendahuluan: Secara Keseluruhan Desa Sinarjaya terdiri dari 10 RW,serta di dukung oleh kondisi tanah yang baik, masyarakat lebih banyak bercocok tanam dan bekerja pabrik. Berdasarkan pemerintah daerah kabupaten (Pemkab) Garut menargetkan prevalensi stunting di bawah 14% pada tahun 2024,sesuai dengan target nasional,meski angka stunting di kabupaten Garut naik dari 23.6% menjadi 24.1% pada tahun 2024 awal berdasarkan Survei Kesehatan Indonesia (SKI). Tujuan: Untuk meningkatkan keterampilan masyarakat dalam menangani luka dan kegawatdaruratan sehari-hari pada anak stunting dengan memanfaatkan tanaman obat keluarga. Metode: Pelaksanaan kegiatan melibatkan warga yang terlibat menjadi Kader PKK dan Kader Posyandu yang ada di Desa Sinarjaya Tarogong Garut. Partisipasinya adalah dalam meningkatkan upaya pemberdayaan masyarakat dalam penanganan kegawatdaruratan sehari-hari dan pemahaman terkait penggunaan TOGA untuk luka pada anak stunting di keluarga khususnya. Kegiatan dilakukan melalui beberapa tahapan, persiapan, pelaksanaan, dan evaluasi. Hasil: Kader dapat mensimulasikan dengan baik dan dapat menjawab pertanyaan dengan baik tentang penanganan kegawatdaruratan. Pelatihan yang berbentuk mini-lecturing dan direct practicing mampu meningkatkan keterampilan menuju aspek kognitif, afektif, serta perilaku mendasar misalnya kemampuan mengingat, perhatian dan mengontrol kinerja. Simpulan: Edukasi melalui pelatihan dan simulasi dapat meningkatkan pengetahuan dan keterampilan kader dalam penanganan kegawatdaruratan sehari-hari dan pemanfaatan TOGA untuk luka. Peningkatan keterampilan dapat meningkatkan kesiapsiagaan dalam penanganan kegawat daruratan. Peran kader PKK dan Posyandu yang dapat menjangkau masyarakat menjadi dasar dalam upaya memberdayakan individu dan keluarga sehingga penanganan akan lebih cepat dan tepat